The Hobby Lobby Amicus Effort - Mariri, Brigitte (Columbia Journal of Gender and Law, 2015)
I’m going to talk a little bit about the cases pending before the Supreme Court that will be heard on March 25. These are two cases brought by for-profit corporations that are challenging part of the Affordable Care Act that requires employers to cover contraception as part of a comprehensive health package. And so I’ll start by talking a little bit about the background of how these cases came about. And I will focus on the amicus efforts in the Supreme Court and the different voices we wanted the Court to hear from, and what we anticipate the Court doing, although for that we can flip a coin and that could be that discussion. But we’ll get there.